Karatekas educated on injury prevention and supported by fitness coaches are more likely to practise injury prevention - Tabben, Montassar; Augustovičová, Dušana; Coquart, Jeremy; Alkhelaifi, Khalid; Chamari, Karim; Arriaza, Rafael (Biology of Sport, 2023)
To determine the current perceptions and practices of top-level karate athletes concerning risk factors and injury prevention programme (IPP) implementation in training and competition. Out of 90 eligible countries(933 athletes) participating in the karate World Senior Championships(WSC) in Madrid 2018, 50 countries (55.6%) represented by 137 athletes (14.7%; 52 females and 85 males) responded to a structured questionnaire. Of the athletes responding, 45% reported that their national team did not conduct any measures to reduce injury risk (43% among females and 47% among males; p = 0.68). Kumite athletes (51%) were more likely to practise injury prevention compared to kata athletes (25%; p = 0.016). Of the respondents, 69%, 60%, 60% and 34% reported having no team doctor, fitness coach, massage therapist and physiotherapist, respectively. A greater proportion of athletes who had access to a fitness coach (part-time or full-time) engaged in injury prevention strategies (67% and 51%, respectively) than those who did not (35%; p = 0.031). Athletes who had received previous advice about injury prevention were more likely to practise injury prevention (58%) compared to the rest (21%; p < 0.001). The current study revealed that: i) almost half of the karatekas already benefited from an injury prevention programme, ii) injury prevention programmes were practised more frequently when there was a fitness coach among their coaching staff, iii) karatekas who had received education about injury prevention were more likely to practise injury prevention programmes.